2014
DOI: 10.1111/bij.12291
|View full text |Cite
|
Sign up to set email alerts
|

Body size influences differently the detectabilities of colour morphs of cryptic prey

Abstract: Body size and coloration may contribute to variation in performance and fitness among individuals; for example, by influencing vulnerability to predators. Yet, the combined effect of size and colour pattern on susceptibility to visual predators has received little attention, particularly in camouflaged prey. In the colour polymorphic pygmy grasshopper Tetrix subulata (Linnaeus, 1758), females are larger than males, although there is a size overlap between sexes. In the present study, we investigated how body s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 54 publications
0
28
1
Order By: Relevance
“…A larger body size could increase detectability by predators (Remmel & Tammaru, 2009;Karpestam et al, 2014), whereas increased body size could limit the size of their predators or, for aposematic species, magnify the warning signals to deter predators (Nilsson & Forsman, 2003). A larger body size could increase detectability by predators (Remmel & Tammaru, 2009;Karpestam et al, 2014), whereas increased body size could limit the size of their predators or, for aposematic species, magnify the warning signals to deter predators (Nilsson & Forsman, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A larger body size could increase detectability by predators (Remmel & Tammaru, 2009;Karpestam et al, 2014), whereas increased body size could limit the size of their predators or, for aposematic species, magnify the warning signals to deter predators (Nilsson & Forsman, 2003). A larger body size could increase detectability by predators (Remmel & Tammaru, 2009;Karpestam et al, 2014), whereas increased body size could limit the size of their predators or, for aposematic species, magnify the warning signals to deter predators (Nilsson & Forsman, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that larger prey sizes generally suffer from higher predation rates, but the predation rate may or may not vary according to the morphological (coloration) characteristics in a given environment (Remmel & Tammaru, 2009;Karpestam et al, 2014). Hence, we also considered different prey sizes and their interaction effects on the effectiveness of camouflage.…”
Section: Introductionmentioning
confidence: 99%
“…The positive effects of functional diversity on colonization success, stability, and persistence of populations (Forsman, , ; Forsman, Betzholtz, & Franzén, ; Forsman & Wennersten, ; Hughes et al., ; Karpestam et al., ) are probably sufficiently strong to outbalance the eroding effect of drift. Additionally, opposing selection in males and females (Forsman, ; Forsman & Appelqvist, ; Karpestam, Merilaita, & Forsman, ) together with the promiscuous mating behavior of pygmy grasshoppers (Caesar, Ahnesjö, & Forsman, ; Johansson, Caesar, & Forsman, ) may prevent the erosion of functional genetic diversity.…”
Section: Discussionmentioning
confidence: 99%
“…; Karlsson et al . ) and perhaps even body size (Karpestam, Merilaita & Forsman ). If these traits also serve as the cue for the detection by a human observer, then intrinsic heterogeneity in detectability will potentially be present in the surveyed populations.…”
Section: Discussionmentioning
confidence: 99%